Effects of a Phosphorus-Binding Feed Supplement on the Blood P and Ca Levels in Dairy Cows - Viktor Jurkovich; Mikolt Bakony; Per Theilgaard; Levente Kovács; Hedvig Fébel (Animals, 2025)
Subclinical hypocalcemia negatively impacts dairy cows’ health, milk production, and reproduction, posing a global challenge. This study evaluated the effects of aluminum sulfate supplementation in the close-up diet to reduce blood phosphorus levels and prevent postpartum hypocalcemia. Thirty-four cows were assigned to the Control (CTRL, n = 17) and Treatment (TRT, n = 17) groups. The TRT group received 400 g/cow/day of aluminum sulfate at least 14 days before calving, with identical post-calving diets. Blood samples were analyzed for total and ionized calcium (tCa, iCa), phosphorus (P), magnesium (Mg), and beta-hydroxybutyrate (BHB). Milk yields were recorded. TRT cows had 0.22, 0.18, and 0.14 mmol/L higher tCa levels than CTRL cows at 12 h, 1 d, and 2 d postpartum, respectively, with elevated iCa levels from 10 days prepartum to 3 days postpartum. Lower serum P levels were observed in TRT cows until day 2 postpartum, while Mg levels remained similar. BHB levels differed only on day 14 postpartum. These findings suggest that aluminum sulfate supplementation effectively lowers serum P and increases tCa, offering a promising strategy for hypocalcemia prevention in dairy cows.